2018
DOI: 10.3390/s18113601
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Image Classification Based on Improved Rotation Forest Algorithm

Abstract: Hyperspectral image classification is a hot issue in the field of remote sensing. It is possible to achieve high accuracy and strong generalization through a good classification method that is used to process image data. In this paper, an efficient hyperspectral image classification method based on improved Rotation Forest (ROF) is proposed. It is named ROF-KELM. Firstly, Non-negative matrix factorization( NMF) is used to do feature segmentation in order to get more effective data. Secondly, kernel extreme lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…If the feature mappings of ELM are unknown for individuals, a kernel trick is performed andKELM has been developed [15]. Figure 3 demonstrated the architecture of KELM.…”
Section: A Kernel Extreme Learning Machinementioning
confidence: 99%
“…If the feature mappings of ELM are unknown for individuals, a kernel trick is performed andKELM has been developed [15]. Figure 3 demonstrated the architecture of KELM.…”
Section: A Kernel Extreme Learning Machinementioning
confidence: 99%
“…In [15], a classification method, called improved Rotation Forest (ROF) is proposed. In this method, Non-negative matrix factorization (NMF) is used to do feature segmentation to get more effective data.…”
Section: A Meta-ensemble Classifier Approach: Randommentioning
confidence: 99%
“…The RoF adopts a principal component analysis (PCA) of feature subtests to reconstruct full feature space and to improve the diversity of all base classifiers, distinguishing it from the RF. Moreover, the RoF has been used for optical and Fully Polarimetric Synthetic Aperture Radar remote sensing classification, and it has been demonstrated that the RoF achieves a higher level of classification accuracy than the RF [21,22]. However, regardless of the many types of classification methods available, each method presents its own advantages and weaknesses [23].…”
Section: Introductionmentioning
confidence: 99%